Teologi Tafsir Ayat Sufistik - Andi Malaka; Ahmad Rifai (Bayani, 2022)
Attention to the interpretation of Sufism and Sufism figures, including how to interpret verses displaying their own interpretation patterns in dynamic scientific patterns, the concept of thinking with the ijtihad approach carried out by Abdul Qadir Al-Jailani and Imam Al-Qursairi in understanding the meaning of the content of the Koran in an isyhari way through the method of approach. intuitive. Tafsir is present as an instrument and tool to carry out scientific studies that discuss various maqasid implied in the Qur'an through various methods of interpretation. The presence of patterns of interpretation and approaches that are taken as evidence of freedom in the interpretation of the Koran without violating the rules of interpretation. The presence of various forms of interpretive approaches in terms of language, philosophy, science of kalam, scientific interpretation and fiqh-sufism and others. In view of the development of the Sufi school taking part in the contribution of Islamic values, the Sufis also interpret the verses of the Koran with an approach to Sufism understanding in a way that they understand and focus on the isyhari method of interpretation or the product of Sufi interpretation by stating its meaning explicitly. In contrast to other types of interpretation, Abdul Qadir Al-Jailani and Imam Al-Qursairi interpret according to Sufi customs, in addition to understanding the Koran from the point of view of the text but also from an emphasis on inner meaning. understand literally.